Supply Chain Network Design by Environmental and Resiliency Requirements - Zu Chang, Li; Hu Cheni, Lee (International journal of industrial engineering and operational research, 2023)
In today's globalized and increasingly interconnected world, supply chain network design plays a vital role in determining the efficiency, sustainability, and resilience of supply chains. With growing concerns over environmental impact and the need to withstand disruptions, integrating environmental and resiliency requirements into supply chain design decisions is of utmost importance. This paper presents a comprehensive study on supply chain network design considering both environmental and resiliency factors. The objective is to develop a framework that enables decision-makers to optimize supply chain design while minimizing environmental footprints and enhancing supply chain resilience.